Analysis of trade opportunities between Bangladesh and New Zealand / Ershad Ali - Ali, Ershad (Universiti Teknologi Mara Selangor, 2019)
Bangladeshi is a low-income developing country in South-East Asia. The country's emerging economy has been earning about 7% GDP growth during the last two decades. On the other hand, New Zealand is a developed western country. Globalization and the competitive business world results from both nations to be more focused on developing trade relationships across the national boundary. This study analyzes the currently ongoing trade relation among these two counties compared to their contribution to the world import and export activities.